Towards the global plastic treaty: a clue to the complexity of plastics in practice - Montserrat Filella; Andrew Turner (Environmental Sciences Europe, 2023)
Abstract Following the decision of the United Nations Environment Assembly (UNEA) to start negotiations for a legally binding treaty to end plastic pollution, discussions and reflections are ongoing on why and how plastic chemicals and polymers of concern should be integrated into the global plastics treaty. One of the points that has been identified as requiring attention is the reduction of the complexity of the composition of plastic objects. This article, addressed to decision-makers and other stake-holders involved in the negotiations, illustrates in a practical and graphical way what complexity means in the case of the presence of inorganic additives.